Real-time assessment of tunnelling-induced damage to structures within the Building Information Modelling Framework - Gamra, Ali (2025)
During the initial design phases of complex multi-disciplinary systems such as urban tunnelling, the appraisal of different design alternatives can ensure optimal designs in terms of costs, construction time, and safety. To enable the evaluation of a large number of design scenarios and to find an optimal solution that minimises the impact of tunnelling on existing structures, the design and assessment process must be efficient, yet provide a holistic view of model interaction, including Soil-Structure Interaction (SSI) effects. In this thesis, an integrated tunnel design tool is proposed for the initial design phases to predict building damage due to ground settlements induced by tunnelling, leveraging empirical and analytical solutions as well as simulation-based meta-models. Furthermore, the visualisation of ground settlements and building damage categories is enabled by integrating these solutions within a Building Information Modelling (BIM) framework for tunnelling. This approach allows for near real-time assessment of structural damage induced by settlements, considering SSI and the non-linear material behaviour of buildings. Because this approach is implemented on a BIM platform for tunnelling, it offers numerous benefits. Firstly, the design can be optimised directly in the design environment, thus eliminating errors in data exchange between designers and computational analysts. Secondly, the effect of tunnelling on existing structures can be effectively visualised within the BIM by producing risk maps and visualising the scaled deformation field, which allows for a more intuitive understanding of design actions and collaborative design. Having a fully parametric design model and real-time predictions, therefore, enables the assessment and visualisation of tunnelling-induced damage for large tunnel